Intracranial pressure monitoring in patients with geriatric trauma may not improve outcome but is associated with increases in resource utilization - Peter Rhee; Chirag Gandhi; Kartik Prabhakaran; Joshua Klein; Bardiya Zangbar; Aryan Rafieezadeh; Ilya Shnaydman; Matthew Bronstein (Trauma Surgery & Acute Care Open)
Background Intracranial pressure (ICP) monitoring (ICPM) is currently recommended for severe traumatic brain injury (TBI). The hypothesis was that ICPM does not change mortality in the geriatric patient population.Methods The Trauma Quality Improvement Program (TQIP) database (2017–2021) was queried to identify intubated geriatric patients (≥65 years of age) with isolated blunt TBI (non-Head Abbreviated Injury Scale (AIS) score <3), with admission Glasgow Coma Scale (GCS) scores of 3–8. Patients with death on arrival or with hospital length of stay <24 hours and patients who underwent craniotomy before ICPM placement were excluded. Favorable discharge disposition was defined as home with or without assistance, and rehabilitation. Propensity score matching (PSM) was performed between ICPM and non-ICPM patients and outcomes were compared. The primary outcome was defined as in-hospital mortality. Secondary outcomes were defined as discharge disposition, hospital length of stay, intensive care unit (ICU) length of stay and ventilator days.Results A total of 19 416 patients met criteria for analysis. ICPM was placed in only 12.1% (n=2363) patients. The Injury Severity Score, GCS and head AIS were similar between the patients with and without monitors. After PSM, we were able to match 2148 patients and there was no difference in mortality between the two groups (52.4% vs 52.1%, p=0.874); however, patients treated with ICPM had significantly longer hospital length of stay (10 (5–17) vs 7 (3–15) days, p<0.001), ICU length of stay (8 (4–14) vs 6 (3–10), p<0.001) and ventilator days (6 (3–11) vs 4 (2–7), p<0.001). Discharge disposition was trending towards unfavorable with increasing age but was similar between the ICPM and No-ICPM groups (p=0.115).Conclusion The usefulness of ICPM in geriatric patients has not yet been shown and would benefit from prospective clinical studies. Minimizing ICPM in geriatric patients may reduce resource burdening without affecting outcome.Level of evidence Level III retrospective study.